ECPA & ECCA Crop Protection European Regulatory Conference 2019. (1st October 2019) - Blake, Robin
The European Crop Protection Association (ECPA) Regulatory Conference 2019 was held in Ghent on 22nd and 23rd May within the framework of the IUPAC Congress, and with the support and participation of the European Crop Care Association (ECCA) and focussed on the many current and future challenges in the implementation and application of Regulation (EC) 1107/2009. The conference was opened with a welcome address by the Director General of the ECPA, Jean-Philippe Azoulay who spoke of his happiness that the annual ECPA regulatory conference was being held alongside the IUPAC conference. He briefly discussed some of the regulatory challenges facing the crop protection industry before highlighting recent progress with respect to transparency and trying to understand public concerns better. The conference was closed by Jean-Philippe Azoulay, who thanked the speakers and organisers, before presenting 11 points by way of conclusion: (1) Our food is safe; (2) The topic of crop protection is complex: difficult to explain in simple words, but easy to simplify and caricature, and requires a differentiated narrative depending on the audience - policy maker vs. general public; (3) The conversation is changing: there is a growing understanding that pesticides are a means to an end and the question is about the production – and consumption – models; (4) Current policy makers only look at the regulation, not at the model or the agronomic or economic impact of their decisions; (5) There are large opportunities for the crop protection industry to contribute to a more sustainable model; (6) Innovative solutions should be encouraged and accelerated, not slowed down; (7) The Sustainable Use Directive is an opportunity for industry to help drive the changes and demonstrate our willingness; (8) No Regulation can address the trust issue – we have to address it ourselves through our actions; (9) Let us acknowledge the end of evidence-based decision making; (10) We need successful farmers now, in the future and for a long time; and (11) The dialogue with retailers and/or consumers is difficult but welcome.